Just one thing : twelve of the world's best investors reveal the one strategy you can't overlook - Mauldin, John (Wiley ; John Wiley [distributor], 2006)
Collects the personal guidance of an outstanding group of recognized financial experts, each offering the single most useful piece of advice garnered from years of investing.